-1=-6x+5x+5

Simple and best practice solution for -1=-6x+5x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1=-6x+5x+5 equation:


Simplifying
-1 = -6x + 5x + 5

Reorder the terms:
-1 = 5 + -6x + 5x

Combine like terms: -6x + 5x = -1x
-1 = 5 + -1x

Solving
-1 = 5 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-1 + x = 5 + -1x + x

Combine like terms: -1x + x = 0
-1 + x = 5 + 0
-1 + x = 5

Add '1' to each side of the equation.
-1 + 1 + x = 5 + 1

Combine like terms: -1 + 1 = 0
0 + x = 5 + 1
x = 5 + 1

Combine like terms: 5 + 1 = 6
x = 6

Simplifying
x = 6

See similar equations:

| 4x-2x+4=24 | | 3x^6-4x^5-152x^4+386x^3+1125x^2-3150x=f(x) | | -1=-6x | | 3x+-7=8+6(x+2) | | 8n-1(2n-3)= | | -5n-7=3n+41 | | 3x^6-4x^5-152x^4+386x^3+1125x^2-3150x=0 | | 4p=63 | | 4(y-1)=4 | | 12=0.25(R) | | 6x^2+21x= | | 9(2m-3)-4(5+3m)=5 | | 4n+3+n=43 | | 4(x-4)+3(1+5x)=-32 | | 22=-was | | 36=-9(6+1) | | -16t^2+76t+5=12t+5 | | 50+85+x=180 | | -27+15-22x=31 | | -3(-c-6)=3c-6 | | 5-x=2x-10 | | y-3+7y=45 | | 1.2x+3.3x=9.2 | | -2(6x-8)=-12x+16 | | 3x+25=4x+5 | | 5m-10-3m=9 | | X-6=2-x | | 2-r=-12 | | 2(0)=6-4x | | 20y=25000 | | 2(7n+3)-2(6+2n)=-46 | | -6=6x+17 |

Equations solver categories